Impact of Leadership versus Organizational Effectiveness in the Secondary Banking Sector in Albania - Shoraj, Dritan; Memetaj, Marionela (European Journal of Economics and Business Studies, 2017)
Through an empirical and theoretical analysis, the study will demonstrate the relationship existing between the leadership style and organizational effectiveness, taking into account that the leadership model explored in this study will be the model provided by Bass and Avolio (1994), represented by the transactional, transformational and laissez-faire style. Impact and behavior of each style on the employees’ motivation, increase of the business organization revenues and finally on the enhancement of organizational effectiveness. The research methodology selected for this study is the quantitative one, where a number of about 450 employees in the secondary banking system in Albania are planned to be interviewed. The measuring instrument will be divided in 4 sections and after data collection, the variable analysis will be realized via SPSS program, which enables the implementation of ANOVA test, Chi-square (?2), means, standard deviations, frequencies and correlations between the key variables to prove the study hypothesis. Finally, this scientific study will be closed with the relevant conclusions and recommendations.